A low complexity OFDM modulator and demodulator based on discrete Hartley transform - Zakaria Sembiring (School of Computer and Communication Engineering, 2011)
The purpose and usefulness of this thesis was formulated as follows; to study the theoretical part of OFDM as the most promising technique for supporting the high speed communication systems; to design a simulation model of low complexity OFDM modulator/demodulator based on discrete Hartley transform as an alternative to replace the complex and mature conventional DFT-OFDM system; to evaluate and analyze the performance of the proposed system with calculation the BER versus SNR under AWGN channel model for several numbers of subcarriers and data sources; to compare the complexity of this system with conventional DFT-OFDM system.